Outcomes of Non-Operative Management Versus Early Surgery in Patients with Adhesive Small Bowel Obstruction: A Comparative Study - Aakif Yousaf, Rashid Minhas, Shahzada Amir Ahmed Babar, Ali Nawaz, Tehwarsham Bin Fayyaz, Afshan Shaikh, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Small bowel obstruction (SBO) is a common general surgical emergency, thought to be responsible for up to 20 per cent of all acute surgical admissions. Objective: To compare the outcomes of non-operative management versus early surgery in patients with ASBO in terms of resolution rates, hospital stay, complications, recurrence, and mortality. Methods: This comparative observational study was conducted at Department of Surgery, Sahiwal Teaching Hospital, Sahiwal from March 2023 to October 2023. A total of 355 patients diagnosed with ASBO were included, with 215 managed non-operatively and 140 undergoing early surgery. Data on demographics, clinical presentation, imaging findings, treatment outcomes, and follow-up were collected. Results: Non-operative management achieved symptom resolution in 86% of patients, while 13.9% required conversion to surgery. The mean hospital stay was significantly shorter in the non-operative group (4.2 ± 1.5 days) compared to the early surgery group (7.6 ± 2.8 days; p < 0.001). Complication rates were lower in the non-operative group (5.6%) than in the early surgery group (20.0%; p = 0.002). In-hospital mortality did not differ significantly between groups (0.5% vs. 1.4%; p = 0.40). Recurrence within six months was significantly higher in the non-operative group (19.5%) compared to the early surgery group (5.7%; p < 0.001). Conclusion: Both non-operative management and early surgical intervention hold distinct advantages in the treatment of adhesive small bowel obstruction. Keywords: Adhesive small bowel obstruction, non-operative management, early surgery, treatment outcomes, recurrence